Wave Processes in Classical and New Solids - Giovine, Pasquale (IntechOpen, 2012)
Wave propagation in solids has been widely studied and principal advances in this field have been achieved not only for the improvements of calculus methods, but also for the high progresses attained in the description of new types of materials. This book presents innovative and original research studies describing some enhancement in both directions. In particular, the first section is devoted to the propagation of waves in complex materials and related dispersion relations are deeply investigated. Instead the second section is dedicated to new applications for the study of wave processes in classical solids; the emphasis is posed on various simulation availabilities in the fields of seismology, damaging, geomaterials and multi-wave propagation. The audience includes students, engineers and advanced scientists with knowledge of wave propagation in solids.